A study on the application of location-based management and automated progress monitoring for linear infrastructure projects - Behnam Manesh, Ali (2016)
Monitoring and controlling linear infrastructure projects is a complex and time consuming task. This demands detailed planning and controlling of schedule tasks at the macro and micro level. This research aims to explore and evaluate the application of location-based management (LBM) theory and an automated progress monitoring system as two micro and macro level solutions for progress monitoring of linear infrastructure projects. The research methodology adopts a qualitative approach for data collection and analysis on an elevated railway project as a linear project in order to implement and evaluate the automated system and LBM progress monitoring framework. The location-based management components were implemented using a location-based software program to implement and evaluate LBM for progress monitoring and also reporting. This thesis also introduced an automated system for progress measurement of large scale linear projects using satellite remote sensing technology. A prototype model was implemented in a small section of an elevated railway project using multi-temporal satellite images. The results and discussion reveal that LBM is an effective tool for implementation of lean construction theory as well as for clear visualization and communication on progress deviations and hence maintaining continuous workflow between locations and crews. The results also demonstrate the application of remote sensing techniques for automatic detection of construction activities in the case study project. The accuracy assessment shows the high accuracy of feature extraction used. The research concludes that the proposed tools are effective for monitoring linear projects. The benefits include implementation of lean philosophy as well as automated progress measurement and improved communication between project participants.